Bilateral vocal fold paresis: the only presenting sign of anti-MUSK antibody myasthenia gravis. Issue 1 (12th January 2021) - Arman, Sam; Kock, Norman; Mochloulis, George; Kanabar, Gorande
Abstract : A previously fit and well 53-year-old man was referred to the otolaryngology clinic with intermittent stridor and was found to have bilateral vocal fold paresis. Subsequent airway compromise necessitated emergency surgical tracheostomy. The man was discharged home with tracheostomy in situ and a diagnosis of idiopathic bilateral vocal cord palsy, as all primary investigations were negative. Neurological disease was suspected following readmission to hospital several weeks later with diplopia. Electromyography and serum antibody testing confirmed a diagnosis of anti-muscle-specific tyrosine kinase antibody positive myasthenia gravis (MuSK-MG); a subset of MG where autoantibodies are directed against MuSK. Resolution of bilateral vocal fold paresis was found 8 months after a short course of immunoglobulin (intravenous immunoglobulin (IVIg)) and daily mycophenolate therapy was commenced. Multidisciplinary teamwork between ear, nose and throat surgeons, neurologists and speech therapists enabled successful decannulation of tracheostomy. The patient has recovered well and remains minimally symptomatic.